MATERIAL AND SUBJECTIVE WELLBEING OF MALAYSIAN HOUSEHOLD: A COMPARATIVE ANALYSIS - Johari, Farah Shazlin; Irpan, Hamidah Muhd; Rasool, Mohamed Saladin Abdul (International Journal of Business and Management Future, 2021)
The concept of wellbeing has attracted many researchers in multi-disciplines. Objective wellbeing particularly focuses on quality of life indicators such as material resources (material wellbeing). While, subjective wellbeing emphasizes on subjective experiences and judgments of individuals in their lives in better ways. In fact, numerous studies have shown several determinants associated with material and subjective wellbeing. To gain better understanding, the purpose of this study is to explore the impact of demographic factors, including age, gender income, education and health status on both material and subjective wellbeing among households. This cross-sectional study was conducted in the district of Alor Gajah, Melaka which had the second highest score of Malaysian Wellbeing Index 2016. By using self-administered questionnaires, the present study employed non-proportionate random sampling involving households. The findings revealed that demographic factors are associated with material and subjective wellbeing.